Developmental of an operationalized checklist of transdiagnostic therapeutic skills for use in general healthcare appointments - Wendy Diana Shoesmith; Assis Kamu; Nicholas Pang Tze Ping (Elsevier Inc., 2025)
Psychotherapy is not available for most people globally with mental disorders. Training general healthcare staff in transdiagnostic psychological intervention skills is a more feasible approach in settings where the access to therapy is low. Tools are needed to measure the use of these skills in general healthcare settings to enable further research into effectiveness. Methods: We operationalized skills taught in a psychological intervention course for general healthcare staff and created a 26-item observational checklist. This was validated using generalizability theory by asking five experts to rate 26 videos. Two research assistants then used the checklist to observe doctors’ consultations before and after a psychological intervention course. We used Rasch analysis to refine the checklist so that it conformed to the Rasch unidimensional measurement model. We analyses the pre-post difference in skill use, and length of appointment using linear mixed modelling. Results: The research assistants observed 87 interviews of 12 doctors before the course and 75 interviews of 11 doctors after the course. The final 18-item checklist had a generalizability coefficient of 86.8% and conformed to the Rasch model. There were 4.28 extra skills on the checklist used per consultation after compared to before the course (95% CI [2.40, 6.16]). The length of appointment did not change. Conclusion: This approach has allowed the development of a flexible checklist, which is valid, reliable and change sensitive, and can be modified and added to by other researchers according to needs. This provides a foundation for further research into effectiveness.